Performance and High Robustness DPC for PWM Rectifier under Unstable Direct Voltage Bus - M.S. Djebbar; H. Benalla (Institute of Advanced Engineering and Science, 2016)
This paper proposes a strategy de controlling a static AC/DC converter based on direct power control (DPC). The instantaneous active and reactive power is controlled in such a way to ensure the PWM rectifier with a sinusoidal current absorption. This control has proven effective in terms of reduction of total harmonic distortion (THD) of current absorbed. Offers a good control of active and reactive power with an operation at unitary power factor. The test of robustness carried out and the results have proven DPC good performance with strong possibility of de integrate it into the field of high voltage and high power as electric traction.